Про залежність розв'язку від параметра виродженої системи диференціальних рівнянь - Потороча, В.В.; Самойленко, В.Г.; Самойленко, Ю.І. (Видавничий дім "Академперіодика" НАН України, 2007)
We prove the theorem on the continuous dependence of a solution to a degenerate system of differential equations on a parameter in the case of non-fulfilment of the condition ''rank-degree''.